2016
DOI: 10.1007/s00408-016-9900-5
|View full text |Cite
|
Sign up to set email alerts
|

Pneumolysin Mediates Platelet Activation In Vitro

Abstract: This study has explored the role of the pneumococcal toxin, pneumolysin (Ply), in activating human platelets. Following exposure to Ply [10-80 nanograms (ng)/ml], platelet activation and cytosolic Ca 2+ concentrations were measured flow cytometrically according to the level of expression of CD62P (P-selectin) and spectrofluorimetrically respectively. Exposure to Ply resulted in marked upregulation of expression of platelet CD62P, achieving statistical significance at concentrations of 40 ng/ml and higher (p<0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 24 publications
3
35
1
Order By: Relevance
“…So far, only the secreted pore-forming toxin pneumolysin could be identified as a platelet activation agent, which is in contrast to the observations made by Keane et al [90]. Pneumolysin (Ply) activated human platelets in vitro via induction of intracellular calcium fluxes and P-selectin expression at concentrations similar to those found in severe pneumococcal infections [94]. However, platelet activation was dependent on pore-formation and did not involve an agonist-receptor mediated outside-to-inside signaling cascade.…”
Section: Pneumococcal and Staphylococcal Interactions With Soluble Plcontrasting
confidence: 50%
“…So far, only the secreted pore-forming toxin pneumolysin could be identified as a platelet activation agent, which is in contrast to the observations made by Keane et al [90]. Pneumolysin (Ply) activated human platelets in vitro via induction of intracellular calcium fluxes and P-selectin expression at concentrations similar to those found in severe pneumococcal infections [94]. However, platelet activation was dependent on pore-formation and did not involve an agonist-receptor mediated outside-to-inside signaling cascade.…”
Section: Pneumococcal and Staphylococcal Interactions With Soluble Plcontrasting
confidence: 50%
“…Authors concluded that the upregulation of the sP‐selectin is secondary to increased levels of bacterial products such as LPS and the pro‐inflammatory stimuli of sNOX2‐dp. Finally, pneumolysin (Ply), a pore‐forming toxin produced by S. pneumoniae , has been recently shown to have the capacity to induce platelet activation, as determined by higher levels of sP‐selectin in tissue culture experiments …”
Section: Mechanisms Of Cardiac Damage During Capmentioning
confidence: 99%
“…PLY, one of the most extensively studied CDCs, exhibits several biological properties, such as activation of the complement system [20], platelets [21], and NLR family pyrin domain containing protein 3 (NLRP3) inflammasome [22] or stimulation of pattern recognition receptors (PRRs) [23,24]. Studies indicated that the pore-forming activity and pathogen-associated molecular pattern (PAMP) activity of the toxin form the foundation for most of the previously mentioned biological properties.…”
Section: Introductionmentioning
confidence: 99%